RELEVANSI KEPATUHAN PENGOBATAN DENGAN KEJADIAN TB MDR DI RUMAH SAKIT UMUM DAERAH EMBUNG FATIMAH KOTA BATAM TAHUN 2019 - Eis Kusmita; Khoirunnisa Munawaroh; Made Tantra; Hazen aziz; Hanafi; Sinta Sari Dewi (Poltekkes Kemenkes Medan, 2022)
MDR TB (multidrug-resistant) is tuberculosis caused by Mycobacterium tuberculosis which has developed immunity to OAT (rifampin and isoniazid). The incidences of MDR TB are an artificial phenomenon (artificial phenomenon) due to inadequate TB treatment. Adherence to TB treatment is a factor that influences the incidence of MDR TB. This study aims to determine the relationship of adherence with the incidence of MDR TB in TB patients with a case-control design. The number of respondents in this study was 20 case respondents and 20 control respondents at Embung Fatimah Hospital, Batam City. The sampling technique used purposive sampling with a non-probability sampling technique. The results of the chi-square test obtained a p-value = 0.004 (< 0.05), then H? is accepted, this indicates that there is a significant relationship between adherence and the incidence of MDR TB in Embung Fatimah Hospital, Batam City in 2019, with an OR value of 7,000 where medication adherence with no category has a seven times greater risk of developing MDR TB. This study concludes that there is a relationship between compliance with the incidence of MDR TB at Embung Fatimah Hospital, Batam City, in 2019. The implication of this study is to identify one of the factors that have a relationship with the incidence of MDR TB to reduce the increase in the incidence of MDR TB. Keywords: Relevance, Compliance, MDR TB, OAT, TB